Numerical modelling of compressible inviscid and viscous flow in turbine cascades - Kozel, Karel; Příhoda, Jaromír (Proceedings of the Conference Algoritmy, 2015)
Mathematical models for inviscid and also viscous transonic flows through turbine cascades are presented. For numerical solution, finite volume upwind explicit (Runge Kutta) and implicit (backward Euler) methods are considered. The flux splitting methods include AUSM, AUSMPW+ and HLLC Riemann solvers. The mathematical models are applied to flow through VKI and SE1050 turbine cascades.